1973
DOI: 10.1055/s-0028-1099425
|View full text |Cite
|
Sign up to set email alerts
|

STIGMASTEROL GLUCOSIDE A CONSTITUENT OFADENANTHERA PAVONINASEED AND LEAF

Abstract: Adenanthera pavonina Li n n. (Mimosaceae) [I], a large deciduous tree, commonly known as 'red wood,' is found in the Eastern Sub-Himalayan tract, the Western Ghats and the Andamans. It is an avenue tree [2] especially in southern part of the country and its wood is used as a dye and as a substitute for the true red sandal wood (Pterocarptls santalintts). The tree yields a gum called m a d at i a [I]; and the seed besides yielding the fixed fat [2], is reported to have medicinal properties [I, 21. While pursuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…was identified as stigrnastero1-ß-Dglucoside through rn.p. and IR properties of the glycoside and its pentaacetate, as well as the rnp., IR and MS properties of the aglycone which accorded well with published data [8].…”
Section: Compound (11)supporting
confidence: 89%
“…was identified as stigrnastero1-ß-Dglucoside through rn.p. and IR properties of the glycoside and its pentaacetate, as well as the rnp., IR and MS properties of the aglycone which accorded well with published data [8].…”
Section: Compound (11)supporting
confidence: 89%
“…This decoction is said to be useful in haemorrhage from the bowels and haematuria 1,2 . Earlier workers [3][4][5][6][7] have reported various chemical constituents from this plant. In the present paper we report the isolation and structural elucidation of a new allelochemical 3,5,7,3',4'-pentahydroxy flavone-3'-O-α-Lrhamnopyranosyl-(1→4)-O-α-L-arabinopyranosyl-(1→3)-Oβ-D-xylopyranoside (1) alongwith two known compounds 2,4,7-trihydroxyisoflavone (2) and isovitexin (3) from methanolic extract of the seeds of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…β-glucopyranoside and quercetin-3-O-rhamnopyranosyl (1''' -> 2'')-βglucopyranoside (Mohammed et al, 2014) stigmasterol glucoside, dulcitol, stigmasterol, octacosanol and glucosides of β-sitosterol (Nigam et al, 1973) Anti-inflammatory (Ara et al, 2010) Antioxidant (Mohammed et al, 2014;Wickramaratne et al, 2016) Anti-quorum sensing (Vasavi et al, 2015) Aleurites , 1998). Also, moluccanic acid, methyl ester moluccanic acid, 6,7-dehydromoluccanic acid (Liu et al, 2008) Stem: Coumarinolignoids extract such as moluccanin (Shamsuddin et al, 1988) Twigs: Moluccanic acid, methyl ester moluccanic acid and 6,7dehydromoluccanic acid (Liu et al, 2008) Cutaneous anti-inflammatory activity (Cesca et al, 2012;Hoepers et al, 2015), antinociceptive (Cesca et al, 2012;Quintao et al, 2011 and2012), bacopaside X, bacoside A3 (Sivaramakrishna et al, 2005) bacopasaponins A-C (Garai et al, 1996) Bidens pilosa L Sesquiterpenes and polyacetylenes E-caryophyllene, β-gurjunene, αhumulene, germacrene-D, biciclogermacrene, α-muurolene, Z-γbisabolene, selina-3,7(11)-diene (Grombone-Guaratini et al, 2005) Stigmasterol, squalene, elaidic and behenic acids, and phytyl heptanoate (Zulueta et al, 1995) Several volatile compounds were found in the hydrodistillate, some Cyclooxygenase and PGE2 inhbitor (Yoshida, 2006) Antioxidant: ROS inhibition and NO activation in dermal endothelial cells (Kohda et al, 2013) antimicrobial (Geissberger & Séquin, 1991) Antioxidant: DPPH, anti-radical and NO inhibitor (Chiang et al, 2004;Cortés-Rojas et al, 2013) immunomodulatory (Chang et al, 2007) anti-aging activity of phytol (Dieamant et al, 2015).…”
Section: Zepernickmentioning
confidence: 99%